Effects of Different Solvents on the Total Phenol Content, Total Flavonoid Content, Antioxidant, and Antifungal Activities of Micromeria graeca L. from Middle Atlas of Morocco - Fatima El Kamari; Hajar El Omari; Karima El-Mouhdi; Amina Chlouchi; Anjoud Harmouzi; Ilham Lhilali; Jihane El Amrani; Chadia Zahouani; Zouhair Hajji; Driss Ousaaid (Biochemistry Research International)
Micromeria graeca L. is a dense chemical source of bioactive compounds such as phenolic compounds, which have various health-related properties. The current study aimed to investigate the impact of different extractor solvents on phenol and flavonoid contents, as well as the antioxidant and antifungal activities of different extracts. Initially, three extractor solvents (methanol, ethyl acetate, and water) were used to prepare the Soxhlet extracts, which were then examined for their polyphenolic content, flavonoid content, and antioxidant potential using three complementary assays (DPPH, FRAP, and TAC). The antifungal capacity against the two fungal strains (Candida albicans and Aspergillus niger) was performed using the method of diffusion on disc. The dosage of phytochemical compounds revealed that the highest values were established in water extract with values of 360 ± 22.1 mg GAE/g dry weight plant and 81.3 ± 21.2 mg RE/g dry weight plant for TPC and TFC, respectively. In addition, the strongest antioxidant activity measured by DPPH and FRAP assays was established in water extract with IC50 values of 0.33 ± 0.23 and 0.23 ± 0.12 mg/mL, respectively, while the methanol extract showed the best antioxidant activity as measured by TAC with an IC50 of 483 ± 17.6 mg GAEq/g dry weight plant. The water extract recorded the most important antifungal activity against Candida albicans with an inhibition zone of 16 ± 1.6 mm and MFC = 500 μg/mL, whereas ethyl acetate extract showed the lowest activity against both studied fungi strains. Micromeria graeca L. contains considerable amounts of bioactive contents with high antioxidant and antifungal potentials, which may make it a promising source of antioxidants and natural antifungal agents.